An Experimental Study on Multipath TCP Congestion Control With Heterogeneous Radio Access Technologies - Monika Prakash (IEEE Access, 2019)
In the near future, a large volume of the data traversing wireless networks will not only be requested and/or reported by humans but also by machines (e.g., the Internet-of-things and machine-to-machine applications). This mandates the availability of enormous radio spectrum resources and an end-to-end reliable information transfer. Currently, many wireless devices are equipped with two wireless interfaces with heterogeneous radio access technologies. Thus, the usage of a transport layer designed for multi-homed devices such as multipath transmission control protocol (MPTCP) is inevitable. This paper presents an experimental performance study of three congestion control algorithms, which can be used by MPTCP, namely, Cubic, linked-increases algorithm (LIA), and opportunistic LIA (OLIA). The testbed comprises real (not simulated) LTE and WiFi networks that are used to connect dual-homed wireless nodes to one another. We comparatively study the throughput performance of the three algorithms under varying factors, including the receiver buffer size, number of parallel connections, data volume, and flow lifetime. Our key findings reveal that, although Cubic is not designed with multipath in mind, it outperforms the multipath-based LIA and OLIA, whenever the LTE per-node capacity is higher than its WiFi counterpart. Also, in a reversed situation (WiFi per-node capacity is higher) Cubic outperforms OLIA and LIA for short-lived flows.